The Sheikh and the Follower (Disciple) in Islamic Mysticism: A Study of the Semiotics of Characters - Zitouni, Faiza; Nedjahi, Nedjela (Arts for Linguistic & Literary Studies, 2021)
This research studies the Sheikh’s character (the Wasel or the Wali), the hero of literary mysticism, and his disciple, the one who desires to follow the mystical path, for clarifying and demonstrating the nature of the relationship between them, which is described as a special kind of relationship, unlike the usual relationship between a student and his teacher in the Arab Islamic heritage. It is more a specific and a spiritual relationship, since the first step in the student’s path, in learning the mystical way, is his strong clinging and true love towards his Sheikh. The research is divided into the following sections: defining the character in light of the semiotic approach, identifying the mystical characters types, and then discussing the two central characters within mystical traditions, namely, the mystical Sheikh first, and then the disciple’s character within mystical traditions. The study then highlights the ethics that the disciple shows in dealing with his Sheikh. Finally, how does the disciple figure out those ethics? And how does he conceive and apply them? The study concluded that the follower must obey his Sheikh, and must not oppose his words and deeds. This created a weak-willed person, whose character is totally melted and vanished in front of his Sheikh.